PEMBELAJARAN KITAB AKHLAQUL LILBANAT DALAM PEMBINAAN AKHLAK SISWA DI SMP ISLAM - Hasanah, Mawardatul; Hasibullah, Muhammad Umar (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research aims to describe the learning of the book of akhlaqul lilbanat in developing students' morals at Al-Mu'ien Islamic Middle School. This study uses a qualitative method. The results of his research showed that the learning of lil banat morals at Al-Mu'ien Islamic Middle School was carried out well. The learning of lil banat morals was specifically aimed at Al-Mu’ien Middle School students because the learning of morals and the development of morals for students have different classes and books. Studying this book in developing students' morals is rare in other schools which specialize in developing students' morals. and the existence of this learning program has proven successful in developing the morals of Al-Mu’ien Middle School students every day, including students being able to be more polite when talking to their teachers, bowing when passing in front of their teachers, and being able to have a more caring nature towards friends and teachers who are affected. disasters such as them following the example of the Prophet's morals towards his friends and so on.